2016
DOI: 10.1371/journal.pone.0164530
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Profiling of Pulmonary Artery in a Rabbit Model of Pulmonary Thromboembolism

Abstract: Acute pulmonary thromboembolism (PTE) refers to the obstruction of thrombus in pulmonary artery or its branches. Recent studies have suggested that PTE-induced endothelium injury is the major physiological consequence of PTE. And it is reasonal to use PTE-induced endothelium injury to stratify disease severity. According to the massive morphologic and histologic findings, rabbit models could be applied to closely mimic the human PE. Genomewide gene expression profiling has not been attempted in PTE. In this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 67 publications
0
17
0
Order By: Relevance
“…The RNA expression profiling dataset of the European rabbit ( Oryctolagus cuniculus ) was obtained from the GEO database in the National Center for Biotechnology Information ( http://www.ncbi.nlm.nih.gov/geo/ ; accession no. GSE84738) ( 13 ). The dataset included eight samples (four control samples and four PTE samples), collected from rabbit pulmonary artery tissue.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The RNA expression profiling dataset of the European rabbit ( Oryctolagus cuniculus ) was obtained from the GEO database in the National Center for Biotechnology Information ( http://www.ncbi.nlm.nih.gov/geo/ ; accession no. GSE84738) ( 13 ). The dataset included eight samples (four control samples and four PTE samples), collected from rabbit pulmonary artery tissue.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, it is reported that troponin I, D-dimer, and plasma tenascin-C are positively correlated with the occurrence of PTE, whereas the erythrocyte sedimentation rate is downregulated in patients with PTE ( 12 ). Tang et al identified interleukin 8 ( IL‑8 ), tumor necrosis factor-α ( TNF‑α ), and C‑X‑C motif chemokine ligand 5 as important factors in PTE in rabbits ( 13 ). In addition, it was revealed that these important genes are associated with cardiovascular disease, pulmonary disease, immune disease, and inflammation ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous studies showed that the expression of FABP4 is increased in an animal model of PTE [ 7 ]. FABP4 is a key enzyme in the regulation of intracellular lipid metabolism and, in turn, lipid metabolism is linked to inflammatory response [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mechanical forces are also implicated in lung diseases, for example, force imbalances arising from pulmonary hypertension can remodel the pulmonary vasculature and induce smooth muscle and fibroblast proliferation in conjunction with increased collagen and elastin protein synthesis and gene expression (Wirtz and Dobbs, 2000). Disturbed mechanical forces exerted on pulmonary vascular endothelial cells induces changes in protein synthesis and expression of pro-inflammatory molecules such as IL-8, TNF-α and CXCL5 (Tang et al, 2016).…”
mentioning
confidence: 99%